William Shakespeare’s Sonnet 130: A Reconsideration - Hasan, Mariwan; Abdulkareem, Lara; Star, Lara (LPPM Universitas Advent Indonesia, 2020)
How to know that a person is in love with someone else? It is usually through expressing one’s love towards the beloved. It will be considered a strong love towards a beloved but if not expressing it or exaggerating it. Shakespeare’s sonnet, in the beginning, is misleading its readers but the ending is a happy one as it is true love between the lovers but not announced everywhere and not exaggerated. This paper aims to analyze one of Shakespeare’s great sonnets “sonnet 130”, which is a satire of Petrarchan sonnets. The paper also looks at the form, and content of the sonnet 130 and analyses it to gain a broader insight into the sonnet. Finally, the study focuses on the literary devices used within the sonnet to comprehend Shakespeare’s portrayal of the image of women in the sonnet.